Effect of Repetitive Transcranial Magnetic Stimulation Combined with Exercise Therapy on the Motor Function in Stroke Patients with Hemiplegia - Wani ZHOU; Lei ZHANG; Rundong LI; Kaiquan XU; Chengji WU (康复学报)
Objective:To discuss the effect of repetitive transcranial magnetic stimulation (rTMS) combined with exercise therapy on the motor function in stroke patients with hemiplegia.Methods:A total of 100 stroke patients with hemiplegia were selected from September 2016 to September 2018, according to the random number table, and they were divided into excitation group and exercise group, with 50 cases in each group. The exercise group was treated with exercise therapy, and the excitation group was treated with rTMS combined with exercise therapy. Before treatment and after 3 months'treatment in the two groups, the latency of motor evoked potential (MEP) and central motor conduction time (CMCT) were measured by magnetic transcranial therapy, the motor function of upper and lower limbs were detected by Fugl-Meyer assessment scale (FMA), the quality of life were detected by activity of daily living scale (ADL), and the electrophysiological indexes, motor function, quality of life of the two groups were compared.Results:There was no significant difference in MEP [ (26.58±3.01) ms and (26.34±2.97) ms], CMCT [ (12.80±1.58) ms and (12.75±1.56) ms] between the excitation group and the exercise group before treatment (P>0.05). The MEP [ (20.15±2.26) ms and (23.24±2.56) ms] and CMCT [ (10.04±1.26) ms and (11.64±1.24) ms] in the excitation group and the exercise group after three months'treatment were significantly lower than those before treatment, the MEP and CMCT in the excitation group after three months'treatment were significantly lower than those in the exercise group, the difference was statistically significant (P<0.001). There was no significant difference in FMA scores of upper limbs [ (22.24±2.66) scores and (22.46±2.72) scores], FMA scores of lower limbs [ (10.31±1.66) scores and (10.23±1.62) scores] between the excitation group and the exercise group before treatment (P>0.05). The FMA scores of upper limbs [ (40.25±4.23) scores and (34.58±3.95) scores] and lower limbs [ (19.36±2.21) scores and (15.26±1.92) scores] in the excitation group and the exercise group after three months'treatment were significantly higher than those before treatment. After three months'treatment, FMA scores of upper limbs and lower limbs in the excitation group were significantly higher than those in the exercise group, with statistically significant differences (P<0.001). There was no significant difference in ADL scores [ (40.91±4.82) and (40.56±4.62) ] between the exercise group and the exercise group before treatment (P>0.05). The ADL scores [ (67.56±7.02) scores and (59.72±6.52) scores] in the exercise group and the exercise group after three months'treatment were significantly higher than those before treatment, and the ADL scores in the excitation group after three months'treatment were higher than those in the exercise group, with statistically significant difference (P<0.001).Conclusions:rTMS combined with exercise therapy can effectively improve the motor neuroelectrophysiological indexes and motor function of stroke patients with hemiplegia, which is conducive to improving the quality of patients'life and worthy of clinical promotion.